Pengembangan Strategi Manajemen Sumber Daya Manusia dalam Transformasi Digital Untuk Meningkatkan Kinerja Perusahaan - Eddy Susanto; Ida Bagus Komang Darma Yudanta; I Made Suparsana; Made Budi Ugiantara; I Gusti A. Made Ari Herawan; I Gede Widana (Syntax Idea)
The background of this research is the significant changes brought about by the fourth industrial revolution and digital transformation, demanding companies to adapt. One crucial aspect of digital transformation is human resource management (HRM). The objective of this research is to develop an appropriate HRM strategy to support digital transformation and enhance company performance. The method employed is a literature review. Data sources are derived from previous research on HRM and digitalization. Content analysis techniques are used to analyze the data sources. The research findings indicate that effective HRM development strategies include improving digital work experiences, providing opportunities for innovation, training, and recognition. Digital transformation positively impacts productivity, customer experience, competitiveness, innovation, and business transparency. Supporting factors and barriers to the implementation of strategies are also analyzed. In conclusion, developing the right HRM strategy can support digital transformation and enhance company performance in the digital era.